The Mechanisms of Alpha‐Amylase Inhibition by Flavan‐3‐Ols and the Possible Impacts of Drinking Green Tea on Starch Digestion. Issue 11 (5th October 2018) - Desseaux, Véronique; Stocker, Pierre; Brouant, Pierre; Ajandouz, El Hassan
Abstract: Many studies have shown that flavan‐3‐ols inhibit mammalian alpha‐amylases but the published IC50 and Ki values vary up to a thousand times. We therefore tested the effects of 6 pure flavan‐3‐ols—abundant in green tea—on the activity of pure porcine pancreatic alpha‐amylase (PPA) under steady‐state kinetic conditions. We used both amylose and maltopentaose as substrates, along with spectrophotometry and chromatography as analytical tools, respectively. A Docking approach was also used to probe the interaction between PPA and each flavan‐3‐ol. The results showed that the 6 flavan‐3‐ols inhibit amylose hydrolysis with Ki comprised between 7 and 34 μM, according to a mixed inhibition profile for gallocatechin gallate, and a competitive inhibition profile for the 5 other flavanols. Only the galloyl‐containing flavan‐3‐ols inhibited the maltopentaose hydrolysis with a Ki of about 30 μM according to a noncompetitive profile. We conclude that dietary flavan‐3‐ols could inhibit starch digestion nonnegligibly. The results of the docking trials were concordant with the kinetic data and have noticeably revealed that the cis ‐flavan‐3‐ols epigallocatechin gallate and epicatechin gallate bind similarly to PPA, involving π‐stacking with Trp59.